2007
DOI: 10.1093/rheumatology/kel255
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-based morphometry of brain SPECT can detect the presence of active central nervous system involvement in systemic lupus erythematosus

Abstract: VBM of BSI is a useful and objective method for detecting perfusion abnormalities in SLE patients, which is indicative of active CNS involvement. However, it is not helpful in differentiating the clinical sub-types of CNS involvement according to the ACR classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…However, as a limitation of the present study, SPECT measurements were qualitatively made. Recently developed quantitative methods for the analysis of SPECT images could help to better understand the mechanisms of cognitive dysfunction in SLE [34, 35]. In addition, lupus anticoagulant, not measured in our study, has been linked to lower cognitive performance in nSLE more specifically than anticardiolipin antibodies [10, 36].…”
Section: Discussionmentioning
confidence: 88%
“…However, as a limitation of the present study, SPECT measurements were qualitatively made. Recently developed quantitative methods for the analysis of SPECT images could help to better understand the mechanisms of cognitive dysfunction in SLE [34, 35]. In addition, lupus anticoagulant, not measured in our study, has been linked to lower cognitive performance in nSLE more specifically than anticardiolipin antibodies [10, 36].…”
Section: Discussionmentioning
confidence: 88%
“…For this analysis, we extracted ReHo values from ROIs selected either, because they presented significantly altered ReHo in this study and/or were previously reported to associate with SLE [Appenzeller et al, 2007a;Emmer et al, 2006]. These values were compared with SLEDAI score and daily GC dosage in individual non-NP-SLE patients; groupwise correlations were analyzed using the Spearman correlation test.…”
Section: Resultsmentioning
confidence: 99%
“…However the authors found a global hypoperfusion in active NPSLE patients compared to healthy controls, which was mainly located in the cortical gray matter. Still, due to the relative nature of the underlying SPECT data, the interpretation of these analyses remains problematical (9). Furthermore, partial voluming effects, inherent to the relatively low spatial resolution of SPECT compared to perfusion weighted MR, cause incorrectly low perfusion values in atrophied areas, i.e., the gray matter.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, previous investigators suggested patchy or random focal hypoperfusion, using single photon emission computed tomography (SPECT) in NPSLE patients (8). A recent study with SPECT suggested that the gray matter in SLE patients was relatively hypoperfused compared to healthy controls (9). On the other hand, Emmi et al (10) reported perfusion abnormalities in patients with severe, mild, and without NP symptoms and concluded that the role of cerebral blood flow (CBF) abnormalities remained unclear.…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%